Implementation of Lettered Picture Card Media to The Language Development of Children Aged 5-6 Years Kindergarten Kartika XIV Siliwangi Cirebon City - Aldi Fachrian; Risbon Sianturi; Gilar Gandana (Journal of Future Education, 2023)
Age plays a crucial role in the language development of children. When children are trained and taught using picture card learning media in their learning process, they become actively engaged and are less likely to feel bored. The materials used in this approach can include materials or even media board letters. By incorporating picture card media, students can develop their language skills, which is of great significance in children's overall development. The writer is particularly interested in utilizing picture card media to enhance the learning experience. The collection of data through observation and language development interviews holds paramount importance, as it is crucial to foster language development from an early age. However, the development of children's language skills may not occur effectively if not properly implemented in the learning process.